Association analysis of FABP1 gene polymorphisms with aspirin-exacerbated respiratory disease in asthma. (1st December 2014) - Chang, Hun Soo; Park, Jong Sook; Shin, Hye-Rim; Park, Byung Lae; Shin, Hyoung Doo; Park, Choon-Sik
ABSTRACT Previously, we used a proteomic approach to demonstrate that the protein level of fatty acid-binding protein 1 (FABP1) is increased in nasal polyps in patients with aspirin-exacerbated respiratory disease (AERD). To reveal the genetic effect of FABP1 variants, we evaluated the association of FABP1 polymorphisms with the risk of AERD in 207 asthmatics with AERD and 1019 aspirin-tolerant asthmatics (ATA). Seven polymorphisms of FABP1 were selected from the National Center for Biotechnology Information (build 36) using minor allele frequency and linkage disequilibrium criteria. The genotype and haplotype distributions were not significantly different between the AERD and ATA groups in all of the genetic models. The percent decline of forced expiratory volume in 1 second (FEV1) after the oral aspirin challenge (OAC) test did not differ according to single-nucleotide polymorphism (SNP) genotypes. In haplotype analysis, asthmatic patients who were BL2ht2 homozygotes showed a greater decline in FEV1 after the OAC test than subjects who possessed 1 or no copy of BL2ht2 (P = 0.035). However, these observations were not significant after correction for multiple comparisons (corrected P value = 1.00). Neither genotype nor haplotype was associated with the presence of nasal polyposis in the study subjects. Although we did not find a significant association between the FABP1 polymorphisms and AERD, our data suggest that the 7 SNPs are not associated with the increased expression of FABP1 in asthmatic patients with AERD. Further studies of epigenetic factors that may contribute to the increased expression of FABP1 in AERD should be performed.